How do sepsis survivors experience life after sepsis? A Danish qualitative study exploring factors of importance - Annmarie Touborg Lassen; Mikkel Brabrand; Christina Østervang; Dorthe Susanne Nielsen; Camilla Schade Skov (BMJ Open)
Objective Sepsis is a condition associated with high mortality and morbidity, and survivors often experience physical and psychological decline. Previous research has primarily focused on sepsis survivors discharged from the intensive care unit (ICU). We aimed to explore and understand the consequences of sepsis experienced by sepsis survivors in general.Design A qualitative study inspired by a phenomenological hermeneutical approach was conducted. Data were analysed using systematic text condensation.Setting Patients with sepsis were identified on admission to the emergency department and invited to an interview 3 months after discharge.Participants Sixteen sepsis survivors were purposively sampled and interviewed. Among these survivors, one patient was admitted to the ICU.Results Three main themes were derived from the analysis: new roles in life, cognitive impairment and anxiety. Although many survivors described a physical decline, they experienced psychological and cognitive impairments after sepsis as the most influential factors in daily life. The survivors frequently experienced fatigue, withdrawals from social activities and anxiety.Conclusion Sepsis survivors’ experiences appeared to overlap regardless of ICU admission or treatment at the general ward. Identifying patients with sepsis-related decline is important to understand and support overall patient processes and necessary in meeting specific needs of these patients after hospital discharge.